Some features of polarization modulation in spectroscopy of optical and photoelectric effects - Kondratenko, S.V.; Matyash, I.A.; Serdega, B.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
We analyze usage of modulation of electromagnetic radiation polarization in investigations of optical and photoelectric effects in anisotropic crystals. It is shown that when transmission spectra are studied with the polarization modulation technique, then the results obtained can be represented as a product of two factors. One of them is the derivative of the transmission coefficient with respect to the absorption coefficient, while another characterizes the absorption coefficient anisotropy. Our analysis demonstrates improved information ability of this technique that enables one to explain some previously obtained results.